2003
DOI: 10.1046/j.1432-1033.2003.03658.x
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic pyrophosphatase in the roundworm Ascaris and its role in the development and molting process of the larval stage parasites

Abstract: Inorganic pyrophosphatase (PPase) is an important enzyme that catalyzes the hydrolysis of inorganic pyrophosphate (PPi) into ortho‐phosphate (Pi). We report here the molecular cloning and characterization of a gene encoding the soluble PPase of the roundworm Ascaris suum. The predicted A. suum PPase consists of 360 amino acids with a molecular mass of 40.6 kDa and a pI of 7.1. Amino acid sequence alignment and phylogenetic analysis indicates that the gene encodes a functional Family I soluble PPase containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
53
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 63 publications
8
53
0
Order By: Relevance
“…However, the reason for increasing heat stability in the presence of Mg 2+ is still unclear. In the previous study, we showed that the rAsPPase absolutely required Mg 2+ for PP i hydrolysis [7]. The maximum enzyme activity was observed with 5 mM Mg 2+ , which then gradually declined with the increasing concentrations of Mg 2+ .…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…However, the reason for increasing heat stability in the presence of Mg 2+ is still unclear. In the previous study, we showed that the rAsPPase absolutely required Mg 2+ for PP i hydrolysis [7]. The maximum enzyme activity was observed with 5 mM Mg 2+ , which then gradually declined with the increasing concentrations of Mg 2+ .…”
mentioning
confidence: 90%
“…Among the Family I PPases, the most well characterized PPases are those from E. coli [8,12] and yeast [4,11,15]. The enzymes have shown strong metal iondependency, with Mg 2+ conferring the highest PP i -hydrolysis activity [4], and sensitive to inhibition by Ca 2+ [17].Recently, we cloned and characterized a gene that encodes a functional Family I PPase of the swine roundworm A. suum [7]. The A. suum PPase (AsPPase) has a molecular mass of 40 kDa and a pI of 7.1, and its homologs were expressed in human and dog roundworms, A. lumbricoides and Toxocara canis respectively.…”
mentioning
confidence: 99%
See 3 more Smart Citations